ERS International Congress, Madrid, 2019: highlights from the Sleep and Clinical Physiology Assembly. Issue 2 (20th July 2020) - Crespo, Andrea; Baillieul, Sébastien; Marhuenda, Esther; Bradicich, Matteo; Andrianopoulos, Vasileios; Zafeiris, Louvaris; Marillier, Mathieu; Almendros, Isaac
The 2019 European Respiratory Society (ERS) International Congress took place in Madrid, Spain, and served as a platform to find out the latest advances in respiratory diseases research. The research aims are to understand the physiology and consequences of those diseases, as well as the improvement in their diagnoses, treatments and patient care. In particular, the scientific sessions arranged by ERS Assembly 4 provided novel insights into sleep-disordered breathing and new knowledge in respiratory physiology. This article, divided by session, will summarise the most relevant studies presented at the ERS International Congress. Each section has been written by Early Career Members specialising in the different fields of this interdisciplinary assembly. A selection of the best sessions from @ERS_assembly4 at the 2019 #ERSCongress by Early Career @EuroRespSoc members https://bit.ly/3g30X6W